The GRR a Fundamental Tool for Dealing with Measurement System Variability - Dian, Milan; Hodinář, Lubomír (Manufacturing Technology Journal, 2018)
With increasing complexity of machinery and products manufacturing the strict requirements for quality and, reliability of the measurement equipment and systems plays significant role in production system and quality assurance in terms of customer satisfaction. In nowadays automotive industry in connection to ISO/TS 16949:2009 there has been observed a strong confrontation with request for proof of suitability for use of selected gauges for a specific operations. An appropriate methodology allowing to determine a gauge the most suitable for a given operation is Gauge Reproducibility and Repeatability study (GRR or R&R). The GRR takes into a consideration the variability of produced parts, operator`s approach, and whole measurement system. The article deals with a description and the adequate methodology, and the experimental implementation of GRR in manufacturing quality process assurance in order to set up and continuously improve the quality level in automotive parts production.
Keywords: quality assurance; measurement variability; GRR; R&R; MSA